"They call me a woodsman": cognitive and social aspects on the relationships between woodsmen and forest researchers - Dantas, Carolina Alencar; Silva, Rafael Ricardo Vasconcelos da; Silveira, Pedro Castelo Branco; Silva, Ana Carolina Borges Lins; Alves, Ângelo Giuseppe Chaves (Ethnobiology and Conservation, 2016)
Woodsmen or "mateiros" are people who are commonly hired or contracted to work as special local collaborators, often guiding scientists inside the forest, providing local names of plants and other useful information. We interviewed forest researchers and woodsmen to unveil the process of forest science production in the coastal zone of Northeast Brazil. The concept of network is used as a basis for discussing the connections involving forest knowledge production in and outside scientific academic environments. We presumed that the so-called social invisibility of woodsmen would be a consequence of the asymmetric relationship they have with formal researchers. Information from the interviews was analyzed by means of thematic coding through the content-analysis technique. We found that the "woodsman" category is mainly an academic construct; a designation attributed generally in an unilateral way by scientific professionals towards some people who work as local experts on plants and other components of forest ecosystems. All of the woodsmen we found were men with a low degree of formal education. Researchers tended to recognize woodsmen as bearers of some indispensable information, although treated as a subordinate and local source of knowledge. Although most researchers realized that woodsmen are key collaborators, most of them never referred explicitly to the aid received from these partners. People from both groups agreed that woodsmen are more and more difficult to find. We suggest that forest researchers dealing with woodsmen should develop a more critical vision on the social relationships in which they are involved while doing fieldwork.